2015
DOI: 10.1134/s0022093015020027
|View full text |Cite
|
Sign up to set email alerts
|

Antiapoptotic effect of gangliosides on PC12 cells exposed to bacterial lipopolysaccharide

Abstract: Lipopolysaccharide (LPS) from the Escherichia coli serotype 0111:B4 at concentrations of 0.1 and 0.125 mg/ml was shown to exert an apoptotic effect on the neuronal PC12 cell line in DMEM (serum free medium). Gangliosides GD1a and GM1 at a concentration of 100 μM were found to raise the PC12 cell line viability and decrease the percentage of PC12 cells in the late-phase apoptosis after exposure to LPS. GD1a and GM1, antiapoptotic effect, flow cytometry. thereby the bacterial LPS-induced DNA fragmentation. Such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…These cells can release neurotransmitters and exhibit properties similar to neurons, providing a model to study neuronal pharmacology. In line with references (Ye et al, 2013;Bayunova et al, 2015), we conducted experiments on a PC12 cell model of LPS-induced injury to study infection in the central nervous system (Mao et al, 2011). MTT results indicated that the injury was concentration-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…These cells can release neurotransmitters and exhibit properties similar to neurons, providing a model to study neuronal pharmacology. In line with references (Ye et al, 2013;Bayunova et al, 2015), we conducted experiments on a PC12 cell model of LPS-induced injury to study infection in the central nervous system (Mao et al, 2011). MTT results indicated that the injury was concentration-dependent.…”
Section: Discussionmentioning
confidence: 99%